The different influence of speed, agility and aerobic capacity toward soccer skills of youth player - Komarudin Komarudin; Suharjana Suharjana; Yudanto Yudanto; Moh Nanang Himawan Kusuma (IP Iermakov S.S., 2022)
Background and Study Aim. The significant influence of speed, agility and aerobic fitness on youth soccer performance is described by current football literature. The sensitive phases of age development of students have been stated to have a different influence compared to professional players. The purpose of this study was to determine the contribution of speed, agility and aerobic fitness on soccer skills to the Student Activity Units (UKM) of Football. Material and Methods. The method used in the correlation research study is a descriptive-quantitative with a cross-sectional approach. The population study was all 35 members of UKM football players and the sample was selected through purposive methods sampling. Furthermore, the instruments to be applied are (1) speed with 30 meters sprint test; (2) agility through a 5-meters shuttle run; (3) aerobic endurance by using the 20m Beep-test protocol; (4) soccer skill using David Lee's test. The SPSS 28 program was used for the statistical operations in the analytical data technique, followed by prerequisite analysis tests, namely the normality test and homogeneity test, as well as a hypothesis test to confirm the hypothesis. Results. The result shows that there is a correlation in positive values between both the independent and dependent variables. Statistical analysis confirms that there is a correlation and positive impact of speed, agility and aerobic capacity of football skills. Significant differences in correlations were found in the speed, agility and aerobic capacity of the participants (p < 0.05). Conclusions. Physical activity based on the anaerobic system has a positive effect on individual skills. In contrast, aerobic capacity plays a role more in the complex skills of football games in real situations.